(untitled) (The South East European Journal of Economics and Business, 2022)
This research assesses perception of corruption in business-to-business and business-to-government inter- actions by using empirical evidence from Serbia. Based on the survey data, it captures the perceptions of corruption of business owners and managers of small and medium enterprises (SMEs) and examines their attitudes towards informal, licit, or illicit, business practices. The typology of SMEs according to their opinion on corruption- and institutional-related obstacles resulted in three different clusters, based on several variables. Moreover, empirical findings show that business is not much hindered by regulations but with a common lack of trust in institutions, crime, and perceived corruption. SMEs are perceived as particularly affected by a negative corrupt environment where large companies are seen as the source of corruption. The findings allow for the creation of lawful and incorruptible business policies, as well as ideas on preventing the common practice of illicit trading with job positions in the public sector.